An integrative literature review on leadership models for innovative organizations - Sacavém, A. (2020)
The main goal of this research is to analyze the type of leadership that can be more effective for innovative organizations. In this case, the research question can have an important meaning for organizations because innovation is a significant issue for the competitiveness of organizations; innovation has many constraints and most often fail because of the type of the leaders. In this context, the research question is, "Which are the most effective leadership styles for innovative organizations?" The methodology used was qualitative based on an integrative literature review, and the results show that paternalistic, authentic, and democratic leaders are the most effective in the support the implementation of innovative processes in organizations.